Forgiveness Therapy to Improve the Meaningfulness of Life Inmates in Prisons - Zuanny, Iyulen Pebry; Subandi, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Inmates experiences various conditions and changes in facing their life. In addition to endure physical burden due to the obstacle in maitaning prior activities, many inmates have undergone psychological burden. Feeling guilty, shameful, hostile, regretful, despair, and pessimistic, they have propensity for anxiety, depression, and even suicidal attempt as the consequence their despair on life. Forgiveness therapy offers understanding and adaptive coping skill, thus, it is expected that inmates will be able to reconcile with themselves, other parties and stressful situation. It also reduces various negative emotions in such a way to provide better view toward life. The study was quasi experiment research which involved one group with double pre-test and post-test consisting of 7 woman inmates who were convicted from Law No. 372-375 of the Criminal Code related to embezzlement or Law 378 of the Criminal Code related to fraud, approximately 23-45 years old, minimum education level of junior high school, and received a period of detention in prison for the first time. Data was analyzed using ANOVA Repeated measure. The result showed that forgiveness therapy was evidenced to be useful in increasing the inmates’ positive view in perceiving meaning of life.